University Student Loyalty Model: Structural Equation Modelling Of Student Loyalty in Autonomous, State, Transformed, and Private Universities in Bangkok - Taecharungroj, Viriya (Scholar: Human Sciences, 2014)
University student’s loyalty is a key factor that contributes to the long-term growth and survivability of the university through financial stability, increased enrolment, and better reputation. The objective of this research is to develop a comprehensive university student loyalty model that incorporates important constructs in a service quality dimension and a relationship quality dimension as well as image and reputation perception. The model is tested using the structural equation modelling approach. The multiple group analysis is conducted to compare the models across different types of university in Bangkok namely, autonomous, state, transformed (Rajabhat and Rajamangala), and private universities. This research collected data from more than 2,400 undergraduate students in the Bangkok Metropolitan area. The University Student Loyalty Model provides university administrators with an objective and practical guideline to formulate an appropriate strategy for their universities.